(untitled) (Research, Society and Development, 2021)
Heavy metals are widely distributed in the environment, and may can find natural, industrial, agricultural and other origins. The accumulation of these metals in water bodies is related to several environmental issues, especially regarding the quality of drinking water. Therefore, the general objective of this study was to isolate, identify and characterize bacteria tolerant to nickel and cobalt metals present in raw water samples and in the sediment of the Rio Traíras - Niquelândia (GO). A total of 68 bacterial isolates were obtained, which were submitted to the microdilution method to determine the minimum inhibitory concentration (MIC). Based on the results found, 12 bacterial choices were chosen, which internationally higher and lower tolerance, being classified according to their microscopic and tinting characteristics. According the results obtained, it is possible to observe the tolerance of isolated bacteria to high concentrations of metals, suggesting its use as a biotechnological tool for the remediation of contaminated areas.